Ubiquitous Intelligence and Computing 7th International Conference, UIC 2010, Xi'an, China, October 26-29, 2010, Proceedings - Yu, Zhiwen; Liscano, Ramiro; Chen, Guanlilng; Zhang, Daqing; Zhou, Xingshe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Ubiquitous sensors, devices, networks and information are paving the way toward a smart world in which computational intelligence is distributed throughout the physical environment to provide reliable and relevant services to people. This ubiquitous intelligence will change the computing landscape because it will enable new breeds of applications and systems to be developed, and the realm of computing possibilities will be significantly extended. By enhancing everyday objects with intelligence, many tasks and processes could be simplified, the physical spaces where people interact, like workplaces and homes, could become more efficient, safer and more enjoyable. Ubiquitous computing, or pervasive computing, uses these many “smart things” or “u-things” to create smart environments, services and applications. A smart thing can be endowed with different levels of intelligence, and may be c- text-aware, active, interactive, reactive, proactive, assistive, adaptive, automated, sentient, perceptual, cognitive, autonomic and/or thinking. Research on ubiquitous intelligence is an emerging research field covering many disciplines. A series of grand challenges exists to move from the current level of computing services to the smart world of adaptive and intelligent services. Started in 2005, the series of UIC conferences has been held in Taipei, Nagasaki, Three Gorges (China), Hong Kong, Oslo and Brisbane. The proceedings contain the papers presented at the 7th International Conference on Ubiquitous Intelligence and Computing (UIC 2010), held in Xi’an, China, October 26–29, 2010. The conference was accompanied by six vibrant workshops on a variety of research challenges within the area of ubiquitous intelligence and computing.
Keynote Speeches -- Programming Pervasive Spaces -- Ubiquitous Experience Media -- The Operating System for the Computer of the 21st Century -- Invited Paper -- Extracting Social and Community Intelligence from Digital Footprints: An Emerging Research Area -- Activity, Localization, and User Identification -- Smart Itinerary Recommendation Based on User-Generated GPS Trajectories -- Inferring User Search Intention Based on Situation Analysis of the Physical World -- GPS Calibrated Ad-Hoc Localization for Geosocial Networking -- Ontology-Enabled Activity Learning and Model Evolution in Smart Homes -- Support Vector Machines for Inhabitant Identification in Smart Houses -- Towards Non-intrusive Sleep Pattern Recognition in Elder Assistive Environment -- Ubiquitous Services and Applications -- The Making of a Dataset for Smart Spaces -- to the Business Processes with Ambient Media - Challenges for Ubiquitous and Pervasive Systems -- A Steerable Tangible Interface and Its Evaluation -- Alerting Accidents with Ambiguity: A Tangible Tabletop Application for Safe and Independent Chemistry Experiments -- Dependency Relation Based Detection of Lexicalized User Goals -- Identification of Gait Patterns Related to Health Problems of Elderly -- Sensor Networks -- An Energy Efficient Localization Strategy for Outdoor Objects Based on Intelligent Light-Intensity Sampling -- RESS: A Data Dissemination Protocol Using Residual Energy and Signal Strength for Wireless Sensor Networks -- Design and Implementation of Mobile Sink Node in SDMA Applications -- RCO: A Multi-channel MAC Protocol with Random Cooperation for Sensor Networks -- Power and Bandwidth Efficiency of IEEE 802.15.4 Wireless Sensor Networks -- Protecting Source Location Privacy in Wireless Sensor Networks with Data Aggregation -- Infrastructure, Middleware and Context-Awareness -- A Middleware for Intelligent Environments and the Internet of Things -- An Infrastructure for Real Objects Augmentation with Additional Personalized Information Services -- A Low-Cost Ubiquitous Family Healthcare Framework -- A Lattice-Theoretic Approach to Runtime Property Detection for Pervasive Context -- Modeling Files with Context Streams -- CASPER: Mining Personalized Services -- Distributed Systems and Services -- A Simple Public-Goods Game Based Incentive Mechanism for Resource Provision in P2P Networks -- A Novel Framework for Service Description and Operations -- A Self-Adaptive Hardware/Software System Architecture for Ubiquitous Computing Applications -- Toward Distributed Declarative Control of Networked Cyber-Physical Systems -- AdContRep: A Privacy Enhanced Reputation System for MANET Content Services -- Context-Awareness Handoff Planning in Heterogeneous Wireless Networks -- Wireless and Mobile Ad hoc Networks -- On the Improving Strategies upon the Route Cache of DSR in MANETs -- LALO: A Link-Aware Lightweight Routing Protocol for Data Delivery in Vehicular Ad Hoc Networks -- POCOSIM: A Power Control and Scheduling Scheme in Multi-Rate Wireless Mesh Networks -- Modeling Contacts and Mobility for Wireless Mobile Networks -- A Method to Improve Adaptability of the Minstrel MAC Rate Control Algorithm -- A New Location-Aware Hierarchical Routing Protocol for MANETs -- Special Session: Ubiquitous Intelligence and Services -- Towards an Efficient and Accurate EEG Data Analysis in EEG-Based Individual Identification -- Activity Recognition on an Accelerometer Embedded Mobile Phone with Varying Positions and Orientations -- A Hybrid Content Delivery Approach for a Mixed Reality Web Service Platform -- Analyzing the Behavioral Structure Characteristics from Web Traffic -- A Smartphone-Based Obstacle Sensor for the Visually Impaired -- SSP: Smart Service Provider A Smart Environment Providing Contextual Services on Android Mobile Devices -- Special Track: Pervasive Social Computing -- Using Cohesive Subgroups for Analyzing the Evolution of the Friend View Mobile Social Network -- Towards Topic-Based Trust in Social Networks -- Mlogger: An Automatic Blogging System by Mobile Sensing User Behaviors -- Managing Workplace Resources in Office Environments through Ephemeral Social Networks -- Contextual Biometric-Based Authentication for Ubiquitous Services.
Keywords: User interfaces (Computer systems).; Computer communication systems; Artificial intelligence; Computers and civilization; Application software; Personal computers; User Interfaces and Human Computer Interaction; Computer Communication Networks; Artificial Intelligence; Computers and Society; Computer Appl. in Social and Behavioral Sciences; Personal Computing